Interrater reliability of the modified Tinkertoy test: A validation study in schizophrenia and control groups - Yasuhisa Nakamura; Reiko Miyamoto; Akihiro Koreki; Sachiko Anamizu; Masaru Mimura (PCN Reports)
Abstract Aim Divergent thinking and executive function are critical components of cognitive performance, necessitating reliable assessment tools to guide clinical decision‐making and research on cognitive deficits. This study aimed to evaluate the interrater reliability of the modified Tinkertoy test (m‐TTT), a neuropsychological tool designed to assess these functions, particularly in individuals with schizophrenia. Methods The interrater reliability of the m‐TTT was assessed in a sample of 40 Japanese participants, including 20 individuals with schizophrenia (12 males, eight females; mean age = 42.4 [standard deviation, 12.6] years) and 20 healthy controls (12 males, eight females; mean age = 40.0 [standard deviation, 9.6] years). Performances were independently scored by two occupational therapists using a standardized framework. Relative reliability was evaluated using intraclass correlation coefficients (ICCs), and absolute reliability was examined using Bland–Altman analysis. Results In the schizophrenia group, ICC values indicated high interrater reliability for complexity (0.979), creation process (0.881), and total (0.969) scores. Similarly, in the control group, ICC values were high for complexity (0.969), creation process (0.790), and total (0.934) scores. Bland–Altman analysis demonstrated no fixed or proportional bias; however, greater variability was observed at higher creation process scores in the control group. Conclusion The results confirm the high interrater reliability of the m‐TTT, supporting its utility as a robust tool for assessing cognitive deficits and guiding rehabilitation strategies in psychiatric contexts. However, the study's generalizability is limited by its Japanese‐only sample, necessitating further validation across diverse populations and cultural settings.